Analisis Penerapan Intensifikasi Pada Tanaman Cabe Di Lahan Tanaman Kopi Masa Pandemi Covid-19 Di Kecamatan Atu Lintang. - Auvi Khaidad; Romano Romano; T. Fauzi (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Planting of coffee crops will be a problem for farmers when coffee crops have not produced. Farmers will lose income for approximately two years before these main crops produce. Through the intensification program of chili and coffee crops are expected to increase and overcome the loss of income of farmers. This study aims to analyze the growth of coffee plants and productivity of intermittent plants, named chili. The method used in this study is Multi Purpose Project (case study). The results of this study showed that the income obtained by farmers in farming intensification of coffee and chili plants in Atu Lintang subdistrict is Rp 47.702.150 on average per farmer / growing season. Coffee and chili intensification farming is worth to run because the B/C Ratio obtained from coffee and chili farming is much greater than 1, which is 4. Production costs amounting to Rp 11.097.850 are only production costs in the first growing season, but farmers only need to spend Rp 10.412.433. Each village spends a different cost to conduct intensification activities of coffee and chili plants.